2018
DOI: 10.1097/md.0000000000012647
|View full text |Cite
|
Sign up to set email alerts
|

Esmolol does not improve quality of postsurgical recovery after ambulatory hysteroscopy

Abstract: Introduction:Intraoperative systemic esmolol has been shown to reduce postsurgical pain. Nonetheless, it is unknown whether the use of intraoperative systemic esmolol can improve patient-reported postsurgical quality of recovery. The main objective of the current investigation was to evaluate the effect of intraoperative esmolol on postsurgical quality of recovery. We hypothesized that patients receiving intraoperative esmolol would report better quality of postsurgical recovery than the ones receiving saline.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…In patients who undergo laparoscopic abdominal surgery, it has been demonstrated that intraoperative administration of esmolol can reduce the need for anesthetics and opioids during surgery and also the occurrence of PONV (27,31,32), which leads to earlier discharge from the hospital and improved patient satisfaction. However, not all authors have reported these benefits for intraoperative beta-blocker administration (33,34). In our study, although the frequency of PONV in the labetalol group was lower than in the remifentanil group, this difference was not statistically significant.…”
Section: Discussioncontrasting
confidence: 74%
“…In patients who undergo laparoscopic abdominal surgery, it has been demonstrated that intraoperative administration of esmolol can reduce the need for anesthetics and opioids during surgery and also the occurrence of PONV (27,31,32), which leads to earlier discharge from the hospital and improved patient satisfaction. However, not all authors have reported these benefits for intraoperative beta-blocker administration (33,34). In our study, although the frequency of PONV in the labetalol group was lower than in the remifentanil group, this difference was not statistically significant.…”
Section: Discussioncontrasting
confidence: 74%
“…32 Rarely, opposite results were published -in patients undergoing gynaecologic laparoscopic surgery esmolol did not assure better recovery from anaesthesia, as compared with the saline infusion. 33 When compared with lidocaine bolus and infusion, esmolol nevertheless also assured better recovery from anaesthesia. 34 There are some reports that esmolol, similarly like local anaesthetic lidocaine, decreases pain and withdrawal movements after the administration of non-depolarising neuromuscular relaxant rocuronium, via yet unclear mechanisms.…”
Section: Discussionmentioning
confidence: 99%